30.3k views
4 votes
Suppose that the functions u and w are defined as follows.u(x) = x +7w(x) = x+8

Suppose that the functions u and w are defined as follows.u(x) = x +7w(x) = x+8-example-1
User Jagb
by
5.1k points

1 Answer

3 votes

\begin{gathered} u(x)=x^2+7 \\ w(x)=\sqrt[]{x+8} \end{gathered}

To find the value of the composed function (u ∘ w) evaluated in 1, we need to compose the functions.


(u\circ w)=u(w(x))

This means wherever we have x in the function u, we need to replace it with the expression for w(x) as follows:


\begin{gathered} (u\circ w)=u(w(x))=w(x)^2+7 \\ \\ (u\circ w)=(\sqrt[]{x+8})^2+7 \end{gathered}

Solving the squared expression:


\begin{gathered} (u\circ w)=x+8+7 \\ \\ (u\circ w)=x+15 \end{gathered}

Now we know the composed function. We just need to evaluate it in x = 1, that is, replace 1 wherever the function has an x:


\begin{gathered} (u\circ w)(1)=1+15 \\ \\ (u\circ w)(1)=16 \end{gathered}

Now we have the first answer: (u ∘ w)(1) = 16.

To find the value of (w ∘ u)(1) we follow the same logic:


(w\circ u)=w(u(x))

In the function w, wherever we have an x, we replace it by the expression for u(x):


\begin{gathered} (w\circ u)=w(u(x))=\sqrt[]{u(x)+8} \\ \\ (w\circ u)=\sqrt[]{(x^2+7)+8}=\sqrt[]{x^2+7+8} \\ \\ (w\circ u)=\sqrt[]{x^2+15} \end{gathered}

Now we know the composed function (w ∘ u). We just need to evaluate it in x = 1, that is, replace 1 wherever the function has an x:


\begin{gathered} (w\circ u)(1)=\sqrt[]{1^2+15}=\sqrt[]{1^{}+15} \\ \\ (w\circ u)(1)=\sqrt[]{16} \\ \\ (w\circ u)(1)=4 \end{gathered}

Now we have the second answer: (w ∘ u)(1) = 4.

User Gyom
by
4.9k points